2014
DOI: 10.1371/journal.pone.0103943
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting of Psychoactive Drugs in Zebrafish Anxiety-Like Behaviors

Abstract: A major hindrance for the development of psychiatric drugs is the prediction of how treatments can alter complex behaviors in assays which have good throughput and physiological complexity. Here we report the development of a medium-throughput screen for drugs which alter anxiety-like behavior in adult zebrafish. The observed phenotypes were clustered according to shared behavioral effects. This barcoding procedure revealed conserved functions of anxiolytic, anxiogenic and psychomotor stimulating drugs and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 57 publications
3
69
2
Order By: Relevance
“…While scototaxis (dark preference) is the most widely tested variable in the light/dark preference test (e.g., Norton et al 2011;Sison and Gerlai 2011;Wong et al 2012), it is not the only observable behavior in this task, and indeed "ethological" variables such as erratic swimming, freezing, thigmotaxis and risk assessment have been shown to be differentially affected by experimental manipulations and pharmacological treatments (Blaser et al 2010;Maximino et al 2010aMaximino et al , 2014bBlaser and Peñalosa 2011). Previous work demonstrated that dark preference is affected by different stressful manipulations, including acute exposure to AS (Mansur et al 2014;Maximino et al 2014a) and chronic unpredictable stress (Chakravarty et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While scototaxis (dark preference) is the most widely tested variable in the light/dark preference test (e.g., Norton et al 2011;Sison and Gerlai 2011;Wong et al 2012), it is not the only observable behavior in this task, and indeed "ethological" variables such as erratic swimming, freezing, thigmotaxis and risk assessment have been shown to be differentially affected by experimental manipulations and pharmacological treatments (Blaser et al 2010;Maximino et al 2010aMaximino et al , 2014bBlaser and Peñalosa 2011). Previous work demonstrated that dark preference is affected by different stressful manipulations, including acute exposure to AS (Mansur et al 2014;Maximino et al 2014a) and chronic unpredictable stress (Chakravarty et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…24 h after stressor exposure animals were individually tested in the light/dark preference test, a model which analyzes zebrafish exploratory behavior under motivational conflict, which has been previously shown to be mediated by the glutamate-nitric oxide pathway (Herculano et al 2014;Maximino et al 2014b). Animals were individually transferred to the central compartment of a black and white tank (15 cm X 10 cm X 45 cm h X d X l) for a 3-min.…”
Section: Light/dark Preferencementioning
confidence: 99%
“…Although recent barcoding/microarray-like approaches in behavioral phenomics may assist with data analyses and interpretation Kokel and Peterson, 2011;Kokel et al, 2012b;Maximino et al, 2014), multidimensional phenotyping such as used here enables the rapid observation, quantification and global examination of zebrafish behavior Cachat, 2013). Furthermore, 3D reconstruction of zebrafish swimming behavior provides a new strategy of pharmacological manipulations, because by analyzing the 3D traces the researchers can now identify similar 3D phenotypes between various drug-treated groups, thus suggesting their shared pharmacological profiles (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that serotonergic projections to the telencephalon compute the aversive expectation value necessary for the zebrafish to mount an active response to aversive stimuli (Amo et al, 2014). Consistent with that hypothesis, drugs which increase 5-HT levels in the zebrafish brain increase defensive behaviour in the light/dark test and decrease it in the novel tank test (Egan et al, 2009;Sackerman et al, 2010;Maximino et al, 2011Maximino et al, , 2013bMaximino et al, , 2014aIturriaga-Vásquez et al, 2012;Kyzar et al, 2013;Stewart et al, 2013;Herculano & Maximino, 2014;Cheng et al, 2016). Moreover, there is a correlation between 5-HT levels in the extracellular fluid ex vivo and behaviour in the light/dark test, with higher levels associated with more defensive behaviour in the light/dark test and less defensive behaviour in the novel tank test (Maximino et al, 2013b).…”
Section: Serotonin and The Aversive Behaviour Network Of Zebrafishmentioning
confidence: 95%